TINJAUAN SYARIAH TERHADAP BADAN HUKUM KOPERASI UNTUK BAITUL MAL WAT TAMWIL (BMT) (Mazahib, 2007)
The improvement of Islamic financial institutions in Indonesia has been grown rapidly. The alternative form such as Baitul Mal wat Tamwil (BMT) is needed to serve this group. The interesting point of BMT is that institution has any relationship with the Cooperative Departement of Indonesia, because the majority of BMTs are based on cooperative form. There were relevant basic concept relationships between cooperatie and BMT management but there was a fundamental different between ooperative and BMTs that is the practice of “Riba”.